Explicit self-esteem mediates the relationship between implicit self-esteem and memory biases in major depression. (30th August 2016) - Romero, Nuria; Sanchez, Alvaro; Vázquez, Carmelo; Valiente, Carmen
Abstract: This study examines the relationships between explicit and implicit self-esteem and self-referent memory biases in depression. We specifically tested the hypothesis that implicit self-esteem would influence depression-related memory biases via its association with explicit self-esteem. Self-esteem was assessed in patients with a current Major Depressive Disorder (MDD; n=38) and in a control group of participants who had never experienced depression (ND; n=40) by using explicit (Rosenberg Self-esteem Questionnaire) and implicit (Go/No-go Association Task) measures. A self-referent processing task of negative and positive adjectives was used to assess memory bias. Our analyses revealed that participants diagnosed with MDD showed lower levels of both explicit and implicit self-esteem in comparison to ND participants. MDD compared to ND participants also recalled a greater number of depressed self-referent adjectives and lower recall of positive self-referent information. Mediation analyses showed an indirect effect of explicit self-esteem on the relationship between implicit self-esteem and depression-related memory biases in the MDD group. These findings suggest an association between implicit and explicit self-esteem in depression that may result in negative cognitive processing, as reflected by self-referent memory biases. Highlights: Depressed patients showed low levels of explicit and implicit self-esteem (SE). Depressed patients were characterized by high recall of depressed adjectives. Depressed patients were also characterized by low recall of positive adjectives. Explicit SE mediated the relationship between implicit SE and memory biases.